PERAN PEREMPUAN DALAM PENGEMBANGAN SAWIT BERKELANJUTAN DALAM BIDANG PENDIDIKAN - Larasati, Tengku Indira; Putra, Wendi Novebri (The Juris, 2025)
This study aims to examine the strategic role of women in the development of sustainable palm oil through education from the perspective of constitutional law. Using a normative juridical approach, the research analyzes constitutional guarantees and legal instruments that affirm women’s rights to education and equal participation in sustainable development. The analysis is based on primary legal materials such as legislation, secondary materials including academic journals, and tertiary sources like legal dictionaries. The findings show that although women significantly contribute to the palm oil sector, their access to education, training, and decision-making positions remains limited due to structural and cultural barriers. The 1945 Constitution of the Republic of Indonesia, along with CEDAW, mandates the state to ensure non-discriminatory access to education and active participation in development. However, current sectoral regulations have yet to fully integrate gender equality, particularly in human resource development. The study concludes that the state must adopt affirmative actions such as training quotas for women, gender-based institutional incentives, and mainstreaming gender perspectives in vocational education curricula. These efforts are essential to positioning women not only as beneficiaries but also as key actors in inclusive and sustainable palm oil development aligned with constitutional justice.